Tracking foraging green turtles in the Republic of the Congo: insights into spatial ecology from a data poor region. Issue 3 (3rd May 2020) - Metcalfe, Kristian; Bréheret, Nathalie; Bal, Gaëlle; Chauvet, Eva; Doherty, Philip D.; Formia, Angela; Girard, Alexandre; Mavoungou, Jean-Gabriel; Parnell, Richard J.; Pikesley, Stephen K.; Godley, Brendan J.
Abstract: Globally, marine turtles are considered threatened throughout their range, and therefore conservation practitioners are increasingly investing resources in marine protected areas to protect key life history stages and critical habitats, including foraging grounds, nesting beaches and inter-nesting areas. Empirical data on the distribution of these habitats and/or the spatial ecology and behaviour of individuals of many marine turtle populations are often lacking, undermining conservation efforts, particularly along the Atlantic coast of Africa. Here we contribute to the knowledge base in this region by describing patterns of habitat use for nine green turtles Chelonia mydas tagged with satellite platform transmitter terminals at a foraging ground in Loango Bay, Republic of the Congo, one of only a few documented mainland foraging grounds for marine turtles in Central Africa. Analyses of these data revealed that core areas of habitat use and occupancy for a wide range of size/age classes were restricted to shallow waters adjacent to Pointe Indienne in Loango Bay, with most individuals showing periods of high fidelity to this area. These data are timely given the Congolese government recently announced its intention to create a marine conservation zone to protect marine turtles in Loango Bay. Despite the small sample size of this study, these data exemplify the need for comprehensive strategies that span national jurisdictions, as we provide the first documented evidence of linkages between green turtle foraging sites in Central Africa (Loango Bay, Republic of the Congo) and Southern Africa (Mussulo Bay, Angola).